Violence Against Children and Child Protection (Case Study in Polres Purworejo) - Justisia Pamilia Luberty (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This study aims to explain the factors that cause of cases of violence against children and legal protection of children's data analysis begins with collecting data, reducing the data, presenting data, and the final conclusion. The results showed that the factors that lead to violence against children that occurred in purworejo refer to acts of sexual violence, which resulted in a deep trauma for the victims, as well as their follow-up is handled purworejo police station. Violence against children in purworejo is a case of sexual act that refers to the handling 76E jo Article 82 by Act No. 23 of 2002 on Child Protection. where the victim is a child and the perpetrator comes from within the family and outside the family. Violence against children should look by the community, in education needed either within the family or outside the family, it affects to grow to Consderng children, because every child deserves the affection in the family environment.Keywords: Violence; Children protection; Families.